Preparation method and application of desert sand ceramic aggregate

Through ball milling, molding, low-temperature presintering, water quenching and high-temperature secondary sintering, combined with pickling treatment, the strength and durability of desert sand ceramic aggregates are solved, and high-strength and rich edges and angles are prepared. Suitable for construction and petroleum and gas extraction, extending service life and improving durability.

CN119263667APending Publication Date: 2025-01-07INNER MONGOLIA UNIV OF TECH +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411380332.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The prior art is difficult to produce high-strength, rich edges and corners of desert sand ceramic aggregates, and the direct use of desert sand as fine aggregates will lead to a shortening of the service life of concrete and asphalt, and desert sand contains harmful impurities that affect durability.

Method used

By adding water ball milling to desert sand raw materials, molding, low-temperature presintering, water quenching and high-temperature secondary sintering, and pickling treatment, we form dense ceramic aggregates, eliminate microcracks and weak phase interfaces, and improve compressive resistance and resistance Corrosive.

Benefits of technology

The prepared ceramic aggregate has high strength, low thermal expansion coefficient, good mechanical properties and durability. It is suitable for concrete, asphalt and polymer mortar, extends service life, and can be used for channel fracturing support in petroleum gas mining. agent.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005069733870000081
    Figure BDA0005069733870000081
  • Figure BDA0005069733870000161
    Figure BDA0005069733870000161
  • Figure BDA0005069733870000171
    Figure BDA0005069733870000171
Patent Text Reader

Abstract

The invention discloses a preparation method of desert sand ceramic aggregate and application of the desert sand ceramic aggregate. The preparation method comprises the following steps: firstly, adding water into a desert sand raw material, and ball-milling to obtain slurry; then the slurry is subjected to forming, sintering treatment and acid pickling treatment in sequence, and ceramic aggregate is obtained after the acid pickling treatment is finished; according to the application of the desert sand ceramic aggregate, the ceramic aggregate prepared by the preparation method of the desert sand ceramic aggregate is used as concrete aggregate, asphalt aggregate or high-molecular polymer mortar aggregate; the ceramic aggregate prepared by the preparation method of the desert sand ceramic aggregate is used as a channel fracturing propping agent in the exploitation industry of petroleum, natural gas, coal bed gas or shale gas, or is used as a heat insulation material in the building industry. By using the method provided by the invention, the desert sand-containing ceramic aggregate with different purposes can be produced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramic aggregate synthesis, in particular to a method for preparing desert sand ceramic aggregate and application of the desert sand ceramic aggregate. Background Art

[0002] Concrete and asphalt are important basic building materials. In concrete and asphalt, sand and stone aggregates account for about 50%-80% of the total volume. They are important components and play a role in improving the compressive strength and durability of the matrix. Infrastructure construction requires a large amount of concrete and asphalt, so the demand for sand and stone aggregates is also increasing. As the source of aggregates, there are currently mainly natural sands including pebbles, crushed stones, river sand, sea sand and mountain sand, and artificial sand and gravel with rich edges and corners made from natural rocks (granite, basalt, etc.) through crushing and screening.

[0003] Natural aggregates must meet the requirements of high strength, high hardness, good durability, clean surface and no impurities and powders. Since natural aggregates are usually made of various rocks and minerals, each rock often contains several phases; for example, granite contains quartz, feldspar, mica, etc., and limestone contains calcite, dolomite, etc. These multi-phase aggregates will crack and break along the interface during service. In addition, the thermal expansion coefficient of natural aggregates is usually (4~10)×10 -6 / ℃, the thermal expansion coefficients of each particle are different due to differences in chemical composition and phase composition; the higher the quartz content, the higher the thermal expansion coefficient of the particle. The thermal expansion coefficient of ordinary cement paste is (10~20)×10 -6 / ℃, so the inconsistency in thermal expansion coefficients between natural aggregate particles and between particles and cement paste will cause temperature changes in the early gelation stage, especially when the ambient temperature changes during service, resulting in cracks at the interface between cement paste and aggregate, thereby deteriorating the service life of concrete.

[0004] In addition, the massive consumption of natural aggregates has led to an increasing shortage of natural sand and gravel resources, and natural rocks cannot be mined without limit; in addition, some plains and deserts are seriously lacking in these resources. Therefore, it is imperative to seek new aggregates to replace existing natural sand and gravel aggregate resources.

[0005] Ceramic aggregates are widely used in the construction and mining industries. They can be added to basic building materials such as concrete, asphalt and some polymer mortars to improve the compressive strength, durability and high temperature resistance of building materials. In addition to being added to concrete and asphalt, some ceramic aggregates of specific shapes, such as spherical ceramic aggregates, are also widely used in the construction industry. Because spherical ceramic aggregates have good fluidity and filling properties, they can be used as thermal insulation materials and fillers. In addition, a large amount of channel fracturing proppants are required in the exploitation of oil, natural gas, coalbed methane and shale gas. These channel fracturing proppants usually use natural sand or high-strength ceramic particles.

[0006] In order to save the production cost of ceramic aggregates, there are some methods of synthesizing ceramic aggregates using low-value raw materials. For example, high-carbon ferrochrome slag, mercury tailings, river mud, Fangzi soil or coke stones are used to make ceramic aggregates. The spinel-forsterite high-strength ceramic aggregate prepared by sintering at 1500℃ for 3h using high-carbon ferrochrome slag as the main raw material has an apparent density of 3100kg / m 3 , water absorption rate is 1.4%, compressive strength is 281.1MPa. According to the weight ratio of mercury tailings: clay = 25 ~ 65: 35 ~ 75, it can be granulated by extrusion granulator and dried by rotary kiln to make ceramic aggregate. There are reports of using river mud, Fangzi soil and coke gemstone as raw materials, keeping warm at 450 ~ 500 ℃ for 20 ~ 30 minutes, and keeping warm at 1100-1180 ℃ for 20-30 minutes to make ceramic aggregate. There are also some methods of directly using waste ceramics from the ceramic industry to crush into fine aggregate for concrete, but due to the complex source of waste ceramics, it is easy to produce inconsistent performance between particles.

[0007] my country has huge reserves of desert sand, and its chemical composition is relatively stable within a certain range. Therefore, using desert sand to synthesize ceramic aggregates has the advantages of a wide source of raw materials, low cost, low aggregate breakage rate and designable performance. It can replace conventional aggregates in construction projects to alleviate the increasingly tight problem of construction aggregates.

[0008] Aggregates can be divided into coarse aggregates and fine aggregates. Desert sand particles are fine, with an average particle size of 100 to 200 microns. At present, there are also a large number of reports on the direct use of desert sand as fine aggregate, but due to the presence of microcracks and weak phase interfaces in desert sand itself, microcracks will expand or new cracks will be generated during service, reducing the service life of concrete and asphalt. In addition, desert sand contains harmful impurities such as clay, mica and carbonate, which are corrosive to the matrix material. Direct use of desert sand as fine aggregate will affect the durability of concrete and asphalt, and can only be used in some non-important occasions. There are reports abroad that fine-grained desert sand is directly sintered to form large-grained aggregates, but because the fine particles are only loosely piled together before sintering, the formation of large particles mainly depends on the melting of the particle surface to bond small particles together. Although it can form a larger sintered body, its shape is irregular, the bonding force is low, it is easy to crush, and the mechanical properties are poor. Summary of the invention

[0009] To this end, the technical problem to be solved by the present invention is to provide a preparation method of desert sand ceramic aggregate and the application of desert sand ceramic aggregate, so as to produce desert sand ceramic aggregate with high strength, rich edges and corners, and suitable for being used as concrete aggregate, asphalt aggregate or polymer mortar aggregate; at the same time, it is also possible to produce channel fracturing proppants with high strength, good corrosion resistance and long service life.

[0010] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0011] The preparation method of desert sand ceramic aggregate is as follows: firstly, the desert sand raw material is ball-milled with water to obtain a slurry; then the slurry is sequentially molded, sintered and pickled, and the ceramic aggregate is obtained after the pickling. The desert sand raw material is formed into powder by ball milling, which can preliminarily eliminate microcracks and weak phase interfaces in the sand particles, so that each phase is evenly distributed, which is conducive to sintering to form a uniform new phase.

[0012] The method for preparing the above-mentioned desert sand ceramic aggregate comprises the following steps:

[0013] Step (1-1), ball milling: adding water to the desert sand raw material and ball milling to obtain a slurry;

[0014] Step (1-2), molding: firstly dry the slurry to a semi-dry state and then crush and sieve to obtain a slurry powder; then press the slurry powder into a plate-like body; pressure molding can reduce the gaps between the dried powders, which is beneficial to the densification of the sintered product.

[0015] Step (1-3), low temperature pre-sintering: the plate-shaped green body is subjected to low temperature pre-sintering to obtain a low temperature pre-sintered green body after the low temperature pre-sintering is completed; when producing angular ceramic aggregate, the green body is first subjected to low temperature pre-sintering, and then the green body after low temperature pre-sintering is crushed and then fired, which is conducive to making the obtained ceramic aggregate dense and improving the compressive performance.

[0016] Step (1-4), water quenching: quickly placing the low-temperature pre-sintered green body into water for water quenching, and further crushing the crushed material obtained after the water quenching to obtain intermediate fragments;

[0017] Step (1-5), high temperature secondary sintering: subjecting the intermediate fragments to high temperature secondary sintering, cooling them to room temperature with the furnace after sintering, and further crushing them to obtain high temperature secondary sintered particles; the sintering temperature of the low temperature pre-sintering is lower than the sintering temperature of the high temperature secondary sintering;

[0018] Step (1-6), pickling treatment: placing the high-temperature secondary sintered particles in an acid solution and stirring for pickling, and washing the high-temperature secondary sintered particles with clean water until they are neutral, that is, ceramic aggregates with edges and corners.

[0019] In the method for preparing the above-mentioned desert sand ceramic aggregate, in step (1-5): the high-temperature secondary sintering temperature is 1200-1250°C.

[0020] In the above-mentioned method for preparing desert sand ceramic aggregate, in step (1-1), the mass ratio of desert sand raw material to water is 1: (1-1.5); the ball milling time is 1-3h;

[0021] In step (1-2), the slurry is dried to a semi-dry state by: placing the slurry at 95-105°C for 24-26 hours; the slurry powder is the sieve under a 200-mesh sieve; the pressing pressure is 20-50 MPa; the thickness of the plate-shaped blank is 10-50 mm;

[0022] In step (1-3), the conditions for low-temperature pre-sintering are: heating to 1100-1200°C at a heating rate of 2-5°C / min, and keeping at 1100-1200°C for 0.5-2h; since desert sand begins to form a liquid phase at about 1100°C, low-temperature pre-sintering is performed within a temperature range of 1100-1200°C. The temperature range of low-temperature pre-sintering is slightly higher than the melting temperature of low-melting-point substances (such as feldspar, glass phase and carbonate, etc.) in the desert sand raw material; during the low-temperature pre-sintering process, the viscous flow of the liquid phase formed by the melting of the low-melting-point substances in the desert sand causes the green body to shrink and densify. While ensuring that a relatively dense ceramic green body is obtained, a relatively short holding time is adopted for the needs of subsequent crushing, so that the sintered body is easy to crack and break through water quenching and it is easier to obtain the required particle size through secondary crushing.

[0023] In step (1-4), the water temperature during water quenching is 20-25° C., and the time from the low-temperature pre-sintered green body leaving the heating furnace to entering the water is less than 5 seconds; the size of the intermediate fragments is 0.5-3.9 mm;

[0024] In step (1-5), the conditions of high-temperature secondary sintering are: heating to 1150-1600°C at a heating rate of 5-10°C / min, and keeping at 1150-1600°C for 0.5-3h; the sintering temperature of low-temperature pre-sintering is lower than the sintering temperature of high-temperature secondary sintering; the processing method of first low-temperature pre-sintering and then high-temperature secondary sintering not only reduces the difficulty of crushing the plate-like blank after low-temperature pre-sintering, but also ensures that the blank obtains sufficiently good mechanical properties and physical properties after sintering. In particular, quartz aggregate is sintered at 1200-1250°C, which can transform α-quartz in desert sand raw materials into a stable quartz phase, reduce the thermal expansion coefficient, and avoid the large volume expansion and contraction caused by the phase change of α-quartz, resulting in microcracks.

[0025] In step (1-6), the acid solution is a hydrochloric acid solution with a mass fraction of HCl of 5wt%; the mass ratio of the hydrochloric acid solution to the high-temperature secondary sintered particles is 5:95; and the stirring time is 30 to 60 minutes. The sintered particles are acid-washed and washed with water to remove impurity elements on the surface of the particles, remove mixed powders and form a rough surface, thereby reducing the adverse effects on the properties of the matrix material. The final screening can obtain particles of different particle size ranges to facilitate the grading combination of aggregates.

[0026] The method for preparing the above-mentioned desert sand ceramic aggregate comprises the following steps:

[0027] Step (2-1), ball milling: adding water to the desert sand raw material and ball milling to obtain a slurry;

[0028] Step (2-2), forming: sieving the slurry and placing it in a granulator for granulation to obtain spherical particles;

[0029] Step (2-3), sintering: spherical particles are sintered, and after the sintering, the particles are cooled to room temperature in a furnace to obtain sintered particles;

[0030] Step (2-4), pickling treatment: placing the sintered particles in an acid solution and stirring for pickling, and washing the sintered particles with clean water until they are neutral, thus obtaining spherical ceramic aggregates.

[0031] In the above-mentioned method for preparing desert sand ceramic aggregate, in step (2-1), the mass ratio of desert sand raw material to water is 1:(1.5-3.5); the ball milling time is 1-3h;

[0032] In step (2-2), the slurry is first passed through a 200-mesh sieve and then placed in a granulator for granulation; during granulation, the rotation speed of the granulator is 1400-2000 rpm, the granulation temperature is 120-350° C., and the granulation time is 10-30 min; the particle size of the spherical particles is 0.5-2.0 mm;

[0033] In step (2-3), the sintering treatment conditions are: heating to 1150-1600° C. at a heating rate of 2-5° C. / min, and keeping at 1150-1600° C. for 1-3 hours;

[0034] In step (2-4), the acid solution is a hydrochloric acid solution with a HCl mass fraction of 5 wt%; the mass ratio of the hydrochloric acid solution to the sintered particles is 5:95; and the stirring time is 30 to 60 minutes.

[0035] In the above-mentioned method for preparing desert sand ceramic aggregate, the desert sand raw material is single desert sand; or the desert sand raw material is a mixture of desert sand and aggregate auxiliary materials, the aggregate auxiliary materials are one or two or more of high alumina mud, magnesite, feldspar, kaolin, silicon carbide, zirconium oxide, clay or industrial solid waste; the industrial solid waste is one or two or more of fly ash, metallurgical slag, tailings and coal gangue.

[0036] In the above-mentioned method for preparing desert sand ceramic aggregate, the desert sand raw material meets any of the following technical indicators:

[0037] (1) The content of quartz phase is 65wt% to 75wt%;

[0038] (2) The content of the mullite phase is 80wt% to 90wt%; the mullite phase contains 68wt% to 74wt% of Al2O3 and 26wt% to 32wt% of SiO2;

[0039] (3) The content of cordierite phase is 75wt% to 85wt%; the cordierite phase contains 11wt% to 15wt% of MgO, 32wt% to 36wt% of Al2O3 and 50wt% to 55wt% of SiO2;

[0040] (4) The content of olivine phase is 80wt% to 85wt%; the olivine phase contains 55wt% to 60wt% MgO and 40wt% to 45wt% SiO2;

[0041] (5) The silicon carbide content is 30wt% to 35wt%.

[0042] Application of desert sand ceramic aggregate: the angular ceramic aggregate prepared by the above-mentioned method for preparing desert sand ceramic aggregate is used as concrete aggregate, asphalt aggregate or polymer mortar aggregate. The polymer mortar can be epoxy resin mortar, polyacrylate mortar, styrene-acrylate emulsion mortar and polyvinyl alcohol cement mortar.

[0043] The application of desert sand ceramic aggregate is to use the spherical ceramic aggregate prepared by the above-mentioned method for preparing desert sand ceramic aggregate as a channel fracturing proppant in the oil, natural gas, coalbed methane or shale gas mining industry, or as a thermal insulation material in the construction industry.

[0044] The technical solution of the present invention achieves the following beneficial technical effects:

[0045] 1. The prepared ceramic aggregate is used as concrete aggregate, asphalt aggregate or polymer mortar aggregate

[0046] 1. In the method for making ceramic aggregate provided in the present invention, the material of the aggregate can be accurately adjusted by batching. The material of the aggregate can be quartz, mullite, olivine or cordierite. Other raw materials such as silicon carbide, zirconium oxide, industrial solid waste, etc. can be added during batching to form a multi-phase composite material, so that the final aggregate has the physical phase characteristics of ceramics (natural aggregates cannot be adjusted), and the specific preparation process of the ceramic aggregate is adjusted to make it have different uses.

[0047] 2. Since the material of the aggregate can be artificially adjusted, the prepared ceramic aggregate can have different mechanical and physical properties, such as high strength, high hardness, high thermal expansion coefficient or low thermal expansion coefficient, etc. or their combination, which can be accurately matched according to the properties of concrete, asphalt and polymer mortar.

[0048] 3. The method for manufacturing ceramic aggregates for asphalt, concrete and high molecular polymer mortar provided by the present invention comprises grinding desert sand or desert sand mixed with other raw materials into powder, compacting the powder into a green body, and then subjecting the green body to low temperature pre-sintering, water quenching and secondary high temperature sintering to form a dense body (i.e., ceramic), which significantly improves the strength and avoids the disadvantage of easily causing concrete cracks when directly using desert sand particles as aggregate; the ceramic aggregate finally obtained has the advantages of rich edges and corners, rough surface, adjustable particle size and adjustable performance.

[0049] 4. The ceramic aggregate used for concrete, asphalt and high molecular polymer mortar in the present invention adopts the preparation process of ball milling-low temperature pre-sintering-water quenching-crushing-high temperature secondary sintering, which eliminates the micro cracks and weak phase interface in the desert sand particles, and obtains ceramic aggregates with uniform composition distribution, rich edges and corners, and high degree of densification. The temperature (1100-1200℃) used for the first sintering (low temperature pre-sintering) is slightly higher than the melting temperature of the low melting point material in the desert sand. Sintering at this temperature can densify the green body. At the same time, the time of low temperature pre-sintering is controlled so that the green body does not produce very high strength and hardness and affect the subsequent crushing for secondary sintering. High temperature secondary sintering uses a higher temperature (1150-1600℃), at which temperature the green body is further densified, and the components in the green body undergo sufficient physical and chemical reactions to form a final stable phase composition, thereby achieving the purpose of improving the mechanical properties and physical properties of ceramic particles. After the raw materials are ball-milled, low-temperature pre-sintering and high-temperature secondary sintering are combined to make the crystals in the ceramic aggregate particles and the glass phase interface tightly bonded together in the form of chemical bonds, without obvious weak interfaces and microcracks, and with strong crack resistance. In addition, impurity elements and impurity phases are mainly dissolved into the glass phase during the sintering process, greatly reducing their adverse effects on the matrix.

[0050] 2. The prepared ceramic aggregate is used as a channel fracturing proppant in the oil, natural gas, coalbed methane or shale gas mining industry, or as a thermal insulation material in the construction industry

[0051] The method for making spherical ceramic aggregate provided in the present invention can produce spherical ceramic aggregate with excellent performance to meet the needs of different fields. Compared with traditional processing methods, this method has the advantages of low raw material cost and environmental protection, and can make full use of waste and industrial solid waste to reduce resource waste. The spherical ceramic aggregate prepared by the method in the present invention has extremely high compressive strength, can withstand high-pressure channel fracturing operations, is not easy to break or deform, thereby ensuring the smooth progress of fracturing operations. Ceramic aggregate has good corrosion resistance, can resist acidic or alkaline fluid corrosion, and has a long service life. The shape of the spherical ceramic aggregate helps to improve its fluidity, reduce blockage and friction resistance, and is conducive to improving the efficiency and success rate of fracturing operations. And the aggregate can maintain a high stability in acidic or alkaline environments, and will not react adversely with oil, gas or formation water. DETAILED DESCRIPTION

[0052] In the following examples, the main components and contents of the desert sand used are shown in Table 1.

[0053] Table 1 Chemical composition of desert sand (mass fraction, mass%)

[0054]

[0055] Example 1

[0056] Desert sand, kaolin and fly ash are used as raw materials, and the raw materials are prepared according to the ratio of about 70wt% quartz phase. The mass ratio of desert sand, kaolin and fly ash is 70:15:15. The above raw materials are put into a ball mill and water is added for ball milling, and the water-to-material mass ratio is 1:1. After ball milling for 2 hours, the slurry is taken out and kept at 100℃ for 24 hours to become a semi-dry state, that is, a dried body is obtained. After the dried body is crushed, the powder with a size of less than 74μm is screened with a 200 mesh sieve and loaded into a forming mold (length × width is 300×300mm), and a plate-shaped green body with a thickness of 50mm is formed under a pressure of 30MPa. When performing low-temperature pre-sintering, the plate-shaped green body is heated to 1120℃ at a rate of 3℃ / min, kept for 1.5 hours, taken out and put into water for water quenching within 5 seconds, and the water temperature during water quenching is 20℃. The green body after water quenching is crushed into pieces with edges and corners (the size of the pieces after the green body is cracked is also relatively large, and there are few small particles). The pieces larger than 4.0 mm are screened out with a 5-mesh screen, and then the powder smaller than 500 μm is screened out with a 35-mesh screen, and finally the intermediate pieces with a size of 0.5 to 4.0 mm are obtained. The intermediate pieces are put into the sintering furnace again and heated to 1150°C at a speed of 5°C / min for 0.5 hours, and then the power is turned off to cool the sintered intermediate pieces to room temperature with the furnace. The sintered intermediate fragments were crushed and then sieved with 5-mesh and 35-mesh sieves to obtain high-temperature secondary sintered particles with a size of 0.5-4.0 mm, and the high-temperature secondary sintered particles were immersed in a hydrochloric acid solution with a mass fraction of 5wt% and stirred for 30 minutes (the ratio of the mass of hydrochloric acid to the mass of the high-temperature secondary sintered particles was 5:95), and the impurities and powder on the surface of the high-temperature secondary sintered particles were removed, and then they were removed and washed with water until the washing liquid was neutral, and the angular desert sand-containing ceramic aggregate was obtained. The compressive strength of the desert sand ceramic aggregate prepared in this embodiment is 70.3MPa; the thermal expansion coefficient is 8.2×10 -6 / ℃, density is 2.5g / cm 3 , alkali solubility is 2.7%, and crushing rate is 15.6% (the crushing rate in this application is tested according to the test method of 7.14 crushing index in GB / T 14684-2022). Alkali solubility in this application: is the reduction in mass of the aggregate after being immersed in 5 mol / L NaOH solution for 24 hours. The aggregate prepared in this embodiment can be used as aggregate for concrete or asphalt.

[0057] Example 2

[0058] Take desert sand, high-alumina mud, magnesite, and feldspar as four raw materials, and mix them according to the fact that the raw materials contain about 80wt% cordierite (2MgO·2Al2O3·5SiO2) (in the cordierite phase: 13.8% Mg0, 34.9% Al2O3, 51.3% SiO2), and the mass ratio of desert sand, high-alumina mud, magnesite, and feldspar is 55:26:12:7. Put the above raw materials into a ball mill and add water to ball mill, and the water-to-material mass ratio is 1:1.2. After ball milling for 1.5 hours, take out the slurry. Keep the slurry at 100℃ for 24 hours to become a semi-dry state, and obtain a dried body. After the dried body is crushed, use a 200-mesh sieve to screen out the powder with a size of less than 74μm and put it into a forming mold (length×width is 300×300mm), and form a plate-shaped blank under a pressure of 20MPa, and the blank thickness is 30mm. During low-temperature pre-sintering, the plate-like green body is heated to 1150°C at a rate of 5°C / min, kept at this temperature for 1 hour, taken out and put into water for water quenching within 5 seconds, and the water temperature during water quenching is 25°C. The green body after water quenching is crushed into angular pieces for the second time, and pieces larger than 2.0mm are screened out with a 10-mesh screen, and powders smaller than 500μm are screened out with a 35-mesh screen, and finally intermediate pieces with a size of 0.5-2.0mm are obtained. The intermediate pieces are put into the sintering furnace again and heated to 1200°C at a rate of 5°C / min and kept at this temperature for 2 hours, and then the power is turned off to allow the sintered intermediate pieces to cool to room temperature with the furnace. The sintered intermediate fragments were crushed and then sieved with 10 mesh and 35 mesh sieves to obtain high-temperature secondary sintered particles with a size of 0.5-2.0 mm, and the high-temperature secondary sintered particles were immersed in a hydrochloric acid solution with a mass fraction of 5wt% and stirred for 60 minutes (the ratio of the mass of hydrochloric acid to the mass of high-temperature secondary sintered particles was 5:95), and impurities and powder on the surface of the high-temperature secondary sintered particles were removed, and then they were removed and washed with water until the washing liquid was neutral, and angular desert sand-containing ceramic aggregates were obtained. The compressive strength of the desert sand ceramic aggregate prepared in this embodiment is 90.1MPa; the thermal expansion coefficient is 3.5×10 -6 / ℃, density is 2.6g / cm 3 , alkali solubility is 3.0%, and crushing rate is 14.9% (the crushing rate in this application is tested according to the test method of 7.14 crushing index in GB / T 14684-2022). The aggregate prepared in this embodiment can be used as aggregate for concrete or asphalt. Alkali solubility in this application: is the reduction in mass of the aggregate after being immersed in 5 mol / L NaOH solution for 24 hours. The aggregate prepared in this embodiment can be used as aggregate for concrete or asphalt.

[0059] Example 3

[0060] Desert sand, high-alumina mud and clay are used as raw materials, and the raw materials are mixed according to the total content of about 84wt% of mullite (3Al2O3·2SiO2) (in the mullite phase: 71.8wt% Al2O3, 28.2wt% SiO2), and the mass ratio of desert sand, high-alumina mud and clay is 35:45:20. The above raw materials are put into a ball mill and ball milled with water, and the water-to-material mass ratio is 1:1.5. After ball milling for 2.5 hours, the slurry is taken out and kept at 100°C for 24 hours to become a semi-dry state, that is, a dried body is obtained. The dried body is crushed and sieved with a 200-mesh sieve to obtain a powder with a size of less than 74 microns, which is loaded into a forming mold (length × width is 300 × 300mm), and a plate-shaped blank with a thickness of 40mm is formed under a pressure of 50MPa. During low-temperature pre-sintering, the plate-shaped green body is heated to 1200°C at a rate of 3°C / min. After being kept warm for 2 hours, it is taken out and placed in water within 5 seconds for water quenching. Water quenching will cause the green body to break. The water temperature during water quenching is 22°C. The green body that has been broken after water quenching is broken into pieces with edges and corners. The pieces larger than 4.0mm are screened out with a 5-mesh screen, and then the powder smaller than 500μm is screened out with a 35-mesh screen. Finally, intermediate pieces with a size of 0.5 to 4.0mm are obtained. The intermediate pieces are put into the sintering furnace again and heated to 1550°C at a rate of 10°C / min for 2.5 hours. Then the power is turned off to cool the sintered intermediate pieces to room temperature with the furnace. The sintered intermediate fragments were crushed and then sieved with 5-mesh and 35-mesh sieves to obtain high-temperature secondary sintered particles with a size of 0.5-4.0 mm. The high-temperature secondary sintered particles were immersed in a hydrochloric acid solution with a mass fraction of 5wt% and stirred for 30 minutes (the ratio of the mass of hydrochloric acid to the mass of the high-temperature secondary sintered particles was 5:95) to remove impurities and powder on the surface of the high-temperature secondary sintered particles, and then removed and washed with water until the washing liquid was neutral, and the angular desert sand-containing ceramic aggregate was obtained. The compressive strength of the desert sand-containing ceramic aggregate prepared in this embodiment is 125.6MPa; the thermal expansion coefficient is 6.3×10 -6 / ℃, the density of aggregate is 2.7g / cm 3 , alkali solubility is 3.3%, and crushing rate is 12.2% (the crushing rate in this application is tested according to the test method of 7.14 crushing index in GB / T 14684-2022). Alkali solubility in this application: is the reduction in mass of the aggregate after being immersed in 5 mol / L NaOH solution for 24 hours. The aggregate prepared in this embodiment can be used as aggregate for concrete or asphalt. The aggregate prepared in this embodiment can be used as aggregate for concrete or asphalt.

[0061] Example 4

[0062] Take desert sand, silicon carbide powder and clay as raw materials, and mix them according to the ratio of 30wt% silicon carbide content in the raw materials. The mass ratio of desert sand, silicon carbide powder and clay is 50:35:15. Put the above raw materials into a ball mill and add water to ball mill, and the water-to-material mass ratio is 1:1. After ball milling for 3 hours, take out the slurry. Keep the slurry at 100℃ for 24 hours to become a semi-dry state, that is, a dried body is obtained. After the dried body is crushed, use a 200-mesh sieve to sieve out the powder with a size of less than 74μm and put it into a forming mold (length × width is 300×300mm), and form a plate-shaped green body under a pressure of 30MPa, and the green body thickness is 10mm. When performing low-temperature pre-sintering, the plate-shaped green body is heated to 1150 at a rate of 4℃ / min and kept warm for 1 hour, taken out and put into water for water quenching within 5 seconds, which will cause the green body to break, and the water temperature during water quenching is 22℃. The water-quenched sintered body is broken into angular fragments, and the fragments larger than 0.9 mm are screened out with a 20-mesh screen, and then the powder smaller than 500 μm is screened out with a 35-mesh screen, and finally the intermediate fragments with a size of 0.5 to 0.9 mm are obtained. The intermediate fragments obtained are put into the sintering furnace again and heated to 1250 at a rate of 5°C / min for 1.5 hours, and then the power is turned off to cool the sintered intermediate fragments to room temperature with the furnace. The sintered intermediate fragments are crushed and then screened with 20-mesh and 35-mesh screens to obtain high-temperature secondary sintered particles with a size of 0.5 to 0.9 mm, and the high-temperature secondary sintered particles are immersed in a hydrochloric acid solution with a mass fraction of 5wt% and stirred for 30 minutes (the mass ratio of hydrochloric acid to the mass of high-temperature secondary sintered particles is 5:95), and the impurities and powder on the surface of the high-temperature secondary sintered particles are removed, and then the particles are removed and washed with water until the washing liquid is neutral, that is, the angular desert sand-containing ceramic aggregate is obtained. The compressive strength of the desert sand ceramic aggregate prepared in this embodiment is 145.4 MPa; the thermal expansion coefficient is 5.1×10 -6 / ℃, density is 2.8g / cm 3 , alkali solubility is 3.0%, and crushing rate is 9.6% (the crushing rate in this application is tested according to the test method of 7.14 crushing index in GB / T 14684-2022). Alkali solubility in this application: is the reduction in mass of the aggregate after being immersed in 5 mol / L NaOH solution for 24 hours. The aggregate prepared in this embodiment can be used as aggregate for concrete or asphalt.

[0063] The ceramic aggregate prepared in the present embodiment has a tight texture, which helps to improve the overall density and stability of concrete and high molecular polymers, and reduce the shrinkage and deformation of concrete. And silicon carbide powder is added during the preparation of ceramic aggregate in the present embodiment, and the compressive strength of aggregate is relatively high, which can enhance the compressive performance of concrete, make concrete and high molecular polymer mixtures more solid and durable, and make asphalt mixtures have better anti-rutting performance, can better withstand the repeated rolling of vehicles, enhance the wear resistance of asphalt mixtures, extend the service life of the road surface, and the surface roughness of ceramic particles is relatively high, which can improve the anti-skid performance of asphalt pavement. And the thermal expansion coefficient of ceramic aggregate obtained in the present embodiment is relatively uniform, which can avoid the problem of cracking of concrete or asphalt matrix caused by uneven expansion and contraction of aggregate. And the alkali solubility of ceramic aggregate in the present embodiment is relatively low, and the tolerance to alkali is higher, which can tolerate the alkaline environment in concrete.

[0064] The angular ceramic aggregate prepared in the above embodiment can be used for concrete and asphalt, and can also be used for polymer mortar. The angular ceramic aggregate particles have good weather resistance and corrosion resistance, can improve the durability of polymer mortar, and improve the construction performance of mortar, such as improving rheology. Irregular ceramic aggregate particles can be embedded in mortar, form mechanical interlocking, enhance the interfacial bonding force and wear resistance of mortar. And the angular ceramic aggregate particles in the above embodiment have good compressive strength, can effectively absorb and disperse stress, and reduce the risk of cracking of mortar.

[0065] Example 5

[0066] Desert sand, high alumina mud and kaolin are used as raw materials. The raw materials contain about 85wt% of mullite (3Al2O3·2SiO2) in total. The mass ratio of desert sand, high alumina mud and kaolin is 35:35:30. The mixed raw materials are put into a ball mill and milled with water. The water-to-material mass ratio is 1:3. After 2 hours of ball milling, the slurry is taken out, and the slurry is passed through a 200 mesh sieve and loaded into a centrifugal granulator. The granulator speed is controlled to 1600rpm and the temperature is 130℃. Keep it for 20min to obtain spherical particles with an average particle size of 1.5mm. The spherical particles are placed in a sintering furnace and heated to 1550℃ at a speed of 3℃ / min for 2.5 hours. Then the power is turned off to cool the spherical particles to room temperature with the furnace. The cooled spherical particles were immersed in a 5wt% hydrochloric acid solution and stirred for 60 minutes (the mass ratio of hydrochloric acid to the mass of the spherical particles was 5:95) to remove impurities and powder on the surface of the spherical particles, and then taken out and washed with water until the washing liquid was neutral to obtain spherical desert sand-containing ceramic aggregate. The compressive strength of the desert sand ceramic aggregate prepared in this embodiment was 120.8MPa; the thermal expansion coefficient was 6.1×10 -6 / ℃, density is 2.5g / cm 3 , sphericity is 0.82, alkali solubility is 1.2%, and crushing rate is 11.5% (the crushing rate in this application is tested according to the test method of 7.14 crushing index in GB / T 14684-2022). Alkali solubility in this application: is the reduction in mass of the aggregate after being immersed in 5 mol / L NaOH solution for 24 hours. The aggregate prepared in this embodiment can be used as aggregate for concrete or asphalt.

[0067] The spherical ceramic aggregate prepared in the present embodiment can be used as a channel fracturing proppant during oil, natural gas, coalbed methane and shale gas exploitation, as well as insulation materials, fillers, etc. required in the construction industry. The spherical ceramic aggregate has extremely high compressive strength, can withstand high-pressure channel fracturing operations, is not easy to break or deform, thereby ensuring the smooth progress of the fracturing operation. The ceramic aggregate has good corrosion resistance, can resist acidic or alkaline fluid corrosion, and has a long service life. The shape of the spherical ceramic aggregate helps to improve its fluidity, reduce blockage and friction resistance, and is conducive to improving the efficiency and success rate of fracturing operations. And the aggregate can maintain a high stability in an acidic or alkaline environment, and will not react adversely with oil, gas or formation water.

[0068] Comparative Example 1

[0069] Quartz sand, kaolin and fly ash are taken as raw materials, and the raw materials are mixed according to the ratio of about 70wt% quartz phase. The mass ratio of quartz sand, kaolin and fly ash is 65:20:15. The above raw materials are put into a ball mill and water is added for ball milling, and the water-to-material mass ratio is 1:1. After ball milling for 2 hours, the slurry is taken out and kept at 100℃ for 24 hours to become a semi-dry state, that is, a dried body is obtained. After the dried body is crushed, the powder with a size of less than 74μm is screened with a 200 mesh sieve and loaded into a forming mold (length × width is 300×300mm), and a plate-shaped green body with a thickness of 50mm is formed under a pressure of 30MPa. When performing low-temperature pre-sintering, the plate-shaped green body is heated to 1120℃ at a rate of 3℃ / min, kept for 1.5 hours, taken out and put into water for water quenching within 5 seconds, and the water temperature during water quenching is 20℃. The green body after water quenching is crushed into angular pieces, and the pieces larger than 4.0 mm are screened out with a 5-mesh screen, and then the powder smaller than 500 μm is screened out with a 35-mesh screen, and finally the intermediate pieces with a size of 0.5 to 4.0 mm are obtained. The intermediate pieces are put into the sintering furnace again and heated to 1150°C at a rate of 5°C / min for 0.5 hours, and then the power is turned off to cool the sintered intermediate pieces to room temperature with the furnace. The sintered intermediate pieces are screened to obtain high-temperature secondary sintered particles with a size of 0.5 to 4.0 mm, and the high-temperature secondary sintered particles are immersed in a hydrochloric acid solution with a mass fraction of 5wt% and stirred for 30 minutes (the mass ratio of hydrochloric acid to the mass of high-temperature secondary sintered particles is 5:95), and the impurities and powder on the surface of the high-temperature secondary sintered particles are removed, and then the particles are removed and washed with water until the washing liquid is neutral, and the quartz sand ceramic aggregate is obtained. The compressive strength of the quartz sand ceramic aggregate prepared in this embodiment is 55.7 MPa; the thermal expansion coefficient is 7.6×10 -6 / ℃, density is 2.2g / cm 3 The alkali solubility of the aggregate is 2.9%, and the crushing rate is 20.4% (the crushing rate in this application is tested according to the test method of 7.14 crushing index in GB / T14684-2022). The alkali solubility in this application is the reduction in mass of the aggregate after being immersed in a 5 mol / L NaOH solution for 24 hours. The aggregate prepared in this embodiment can be used as aggregate for concrete or asphalt.

[0070] The ceramic aggregate prepared in this comparative example can be used as aggregate for concrete or asphalt. The preparation method of the aggregate in this comparative example is basically the same as that in Example 1, but no desert sand is added, and the desert sand is replaced by quartz sand. Compared with desert sand, quartz sand has a higher purity, and the components introduced into the raw material that can cause sintering density are reduced, resulting in a decrease in the density of the ceramic aggregate, which ultimately leads to a significant decrease in the compressive strength and density of the ceramic aggregate prepared in this comparative example compared with that in Example 1, and the sphericity of the particles in Comparative Example 1 is higher, and the edges and corners are not rich enough. Compared with Example 1, the ceramic aggregate in this comparative example has a limited effect on improving the compressive capacity of asphalt or concrete substrates.

[0071] Comparative Example 2

[0072] Quartz sand, high-alumina mud, magnesite and feldspar are taken as four raw materials, and the ingredients are prepared according to the total content of about 80wt% cordierite (2MgO·2Al2O3·5SiO2) in the raw materials (in the cordierite phase: 13.8% Mg0, 34.9% Al2O3, 51.3% SiO2). The mass ratio of quartz sand, high-alumina mud, magnesite and feldspar is 46:32:12:10. The above raw materials are put into a ball mill and ball milled with water, and the water-to-material mass ratio is 1:1.2. After ball milling for 1.5 hours, the slurry is taken out. The slurry is kept at 100℃ for 24 hours to become a semi-dry state, and a dried body is obtained. After the dried body is crushed, the powder with a size of less than 74μm is sieved with a 200-mesh sieve and loaded into a forming mold (length × width is 300×300mm), and a plate-shaped blank is formed under a pressure of 20MPa, and the blank thickness is 30mm. During low-temperature pre-sintering, the plate-like green body is heated to 1150°C at a rate of 5°C / min, kept at this temperature for 1 hour, taken out and put into water for water quenching within 5 seconds, and the water temperature during water quenching is 25°C. The green body after water quenching is crushed into angular pieces for the second time, and pieces larger than 2.0mm are screened out with a 10-mesh screen, and powders smaller than 500μm are screened out with a 35-mesh screen, and finally intermediate pieces with a size of 0.5-2.0mm are obtained. The intermediate pieces are put into the sintering furnace again and heated to 1200°C at a rate of 5°C / min and kept at this temperature for 2 hours, and then the power is turned off to allow the sintered intermediate pieces to cool to room temperature with the furnace. The sintered intermediate fragments were sieved to obtain high-temperature secondary sintered particles with a size of 0.5 to 2.0 mm, and the high-temperature secondary sintered particles were immersed in a hydrochloric acid solution with a mass fraction of 5wt% and stirred for 60 minutes (the mass ratio of hydrochloric acid to the mass of high-temperature secondary sintered particles was 5:95), and impurities and powder on the surface of the high-temperature secondary sintered particles were removed, and then the particles were taken out and washed with water until the washing liquid was neutral, and quartz sand ceramic aggregate was obtained. The compressive strength of the quartz sand ceramic aggregate prepared in this embodiment is 76.2MPa; the thermal expansion coefficient is 2.9×10 -6 / ℃, the density of aggregate is 2.3g / cm 3, alkali solubility is 3.3%, and crushing rate is 18.8% (the crushing rate in this application is tested according to the test method of 7.14 crushing index in GB / T 14684-2022). Alkali solubility in this application: is the reduction in mass of the aggregate after being immersed in 5 mol / L NaOH solution for 24 hours. The aggregate prepared in this embodiment can be used as aggregate for concrete or asphalt.

[0073] The ceramic aggregate prepared in this comparative example can be used as aggregate for concrete or asphalt. The preparation method of aggregate in this comparative example is basically the same as that in Example 2, but desert sand is not added, but desert sand is replaced with quartz sand. Compared with desert sand, quartz sand has a higher purity, and the impurity components introduced into the raw material that can cause sintering density are reduced, resulting in a lower density of the ceramic aggregate, which ultimately leads to a decrease in the compressive strength and density of the ceramic aggregate prepared in this comparative example compared with those in Example 2, and the sphericity of the particles in Comparative Example 2 is higher, and the edges and corners are not rich enough. Compared with Example 2, the ceramic aggregate in this comparative example has a limited effect on improving the compressive capacity of asphalt or concrete substrates, and its ability to withstand alkaline environments is also low.

[0074] Comparative Example 3

[0075] Take quartz sand, high alumina mud and kaolin as raw materials, and prepare the materials according to the total content of about 85wt% mullite (3Al2O3·2SiO2) in the raw materials (in the mullite phase: 71.8wt% Al2O3, 28.2wt% SiO2), and the mass ratio of quartz sand, high alumina mud and kaolin is 32:36:32. Put the mixed raw materials into a ball mill and add water for ball milling, and the water-to-material mass ratio is 1:3. After ball milling for 2 hours, take out the slurry, pass the slurry through a 200 mesh sieve and put it into a centrifugal granulator, control the granulator speed to 1600rpm, the temperature to 130℃, keep it for 20min, and obtain spherical particles with an average particle size of 1.5mm. Put the spherical particles into a sintering furnace and heat them to 1550℃ at a speed of 3℃ / min for 2.5 hours, then turn off the power and let the spherical particles cool to room temperature with the furnace. The cooled spherical particles were immersed in a 5wt% hydrochloric acid solution and stirred for 60 minutes (the mass ratio of hydrochloric acid to the mass of the spherical particles was 5:95) to remove impurities and powder on the surface of the spherical particles, and then taken out and washed with water until the washing liquid was neutral to obtain a spherical quartz sand-containing ceramic aggregate. The compressive strength of the quartz sand ceramic aggregate prepared in this embodiment was 112.6MPa; the thermal expansion coefficient was 5.8×10 -6 / ℃, density is 2.3g / cm 3The sphericity of the particles is 0.82, the alkali solubility is 1.4%, and the crushing rate is 16.9% (the crushing rate in this application is tested according to the test method of 7.14 crushing index in GB / T 14684-2022). The alkali solubility in this application is the reduction in mass of the aggregate after being immersed in a 5 mol / L NaOH solution for 24 hours. The aggregate prepared in this embodiment can be used as aggregate for concrete or asphalt.

[0076] Compared with Example 5, the desert sand is replaced by quartz sand in this comparative example. Compared with desert sand, quartz sand has higher purity, less impurity components introduced into the raw material that can cause sintering density, and the density of the aggregate is reduced. Finally, the density and compressive strength of the spherical ceramic aggregate obtained in this comparative example are both lower than those in Example 5. This shows that the spherical ceramic aggregate in Example 5 has better compressive performance and can better tolerate alkaline environment.

[0077] Table 1 Comparison of performance parameters of embodiments and comparative examples

[0078]

[0079]

[0080] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the claims of this patent application.

Claims

1. A method for preparing desert sand ceramic aggregate, characterized in that: Firstly, the desert sand raw material is added with water and ball-milled to obtain a slurry; then the slurry is subjected to molding, sintering treatment and pickling treatment in sequence, and ceramic aggregate is obtained after the pickling treatment is completed.

2. The method for preparing desert sand ceramic aggregate according to claim 1, characterized in that: The steps include: Step (1-1), ball milling: adding water to the desert sand raw material and ball milling to obtain a slurry; Step (1-2), molding: first drying the slurry to a semi-dry state, then crushing and sieving to obtain a slurry powder; then pressing the slurry powder into a mold to obtain a plate-shaped green body; Step (1-3), low temperature pre-sintering: performing low temperature pre-sintering on the plate-shaped green body, and obtaining a low temperature pre-sintered green body after the low temperature pre-sintering is completed; Step (1-4), water quenching: quickly placing the low-temperature pre-sintered green body into water for water quenching, and further crushing the crushed material obtained after the water quenching to obtain intermediate fragments; Step (1-5), high temperature secondary sintering: subjecting the intermediate fragments to high temperature secondary sintering, cooling them to room temperature with the furnace after sintering, and further crushing them to obtain high temperature secondary sintered particles; the sintering temperature of the low temperature pre-sintering is lower than the sintering temperature of the high temperature secondary sintering; Step (1-6), pickling treatment: placing the high-temperature secondary sintered particles in an acid solution and stirring for pickling, and washing the high-temperature secondary sintered particles with clean water until they are neutral, that is, ceramic aggregates with edges and corners.

3. The method for preparing desert sand ceramic aggregate according to claim 2, characterized in that: In step (1-1), the mass ratio of desert sand raw material to water is 1:(1-1.5); the ball milling time is 1-3h; In step (1-2), the slurry is dried to a semi-dry state by: placing the slurry at 95-105°C for 24-26 hours; the slurry powder is the sieve under a 200-mesh sieve; the pressing pressure is 20-50 MPa; the thickness of the plate-shaped blank is 10-50 mm; In step (1-3), the conditions for low-temperature pre-sintering are: heating to 1100-1200° C. at a heating rate of 2-5° C. / min, and keeping at 1100-1200° C. for 0.5-2 h; In step (1-4), the water temperature during water quenching is 20-25° C., and the time from the low-temperature pre-sintered green body leaving the heating furnace to entering the water is less than 5 seconds; the size of the intermediate fragments is 0.5-3.9 mm; In step (1-5), the conditions for high-temperature secondary sintering are: heating to 1150-1600°C at a heating rate of 5-10°C / min, and keeping at 1150-1600°C for 0.5-3h; the sintering temperature of the low-temperature pre-sintering is lower than the sintering temperature of the high-temperature secondary sintering; In step (1-6), the acid solution is a hydrochloric acid solution having a mass fraction of HCl of 5 wt%; The mass ratio of the hydrochloric acid solution to the high-temperature secondary sintered particles is 5:95; the stirring time is 30 to 60 minutes.

4. The method for preparing desert sand ceramic aggregate according to claim 3, characterized in that: In step (1-5): the high-temperature secondary sintering temperature is 1200-1250°C.

5. The method for preparing desert sand ceramic aggregate according to claim 1, characterized in that: The steps include: Step (2-1), ball milling: adding water to the desert sand raw material and ball milling to obtain a slurry; Step (2-2), forming: sieving the slurry and placing it in a granulator for granulation to obtain spherical particles; Step (2-3), sintering: spherical particles are sintered, and after the sintering, the particles are cooled to room temperature in a furnace to obtain sintered particles; Step (2-4), pickling treatment: placing the sintered particles in an acid solution and stirring for pickling, and washing the sintered particles with clean water until they are neutral, thus obtaining spherical ceramic aggregates.

6. The method for preparing desert sand ceramic aggregate according to claim 5, characterized in that: In step (2-1), the mass ratio of desert sand raw material to water is 1:(1.5-3.5); the ball milling time is 1-3h; In step (2-2), the slurry is first passed through a 200-mesh sieve and then placed in a granulator for granulation; during granulation, the rotation speed of the granulator is 1400-2000 rpm, the granulation temperature is 120-350° C., and the granulation time is 10-30 min; the particle size of the spherical particles is 0.5-2.0 mm; In step (2-3), the sintering treatment conditions are: heating to 1150-1600° C. at a heating rate of 2-5° C. / min, and keeping at 1150-1600° C. for 1-3 hours; In step (2-4), the acid solution is a hydrochloric acid solution with a HCl mass fraction of 5 wt%; the mass ratio of the hydrochloric acid solution to the sintered particles is 5:95; and the stirring time is 30 to 60 minutes.

7. The method for preparing desert sand ceramic aggregate according to any one of claims 1 to 6, characterized in that: The desert sand raw material is single desert sand; or the desert sand raw material is a mixture of desert sand and aggregate auxiliary materials, the aggregate auxiliary materials are one or a mixture of two or more of high alumina mud, magnesite, feldspar, kaolin, silicon carbide, zirconium oxide, clay or industrial solid waste; the industrial solid waste is one or a mixture of two or more of fly ash, metallurgical slag, tailings and coal gangue.

8. The method for preparing desert sand ceramic aggregate according to claim 7, characterized in that: Desert sand raw materials meet any of the following technical indicators: (1) The content of quartz phase is 65wt% to 75wt%; (2) The content of the mullite phase is 80wt% to 90wt%; the mullite phase contains 68wt% to 74wt% of Al2O3 and 26wt% to 32wt% of SiO2; (3) The content of the cordierite phase is 75wt% to 85wt%; the cordierite phase contains 11wt% to 15wt% of MgO, 32wt% to 36wt% of Al2O3 and 50wt% to 55wt% of SiO2; (4) The content of olivine phase is 80wt% to 85wt%; the olivine phase contains 55wt% to 60wt% MgO and 40wt% to 45wt% SiO2; (5) The silicon carbide content is 30wt% to 35wt%.

9. Application of desert sand ceramic aggregate, characterized in that: The ceramic aggregate prepared by the method for preparing desert sand ceramic aggregate according to any one of claims 1 to 4 is used as concrete aggregate, asphalt aggregate or high molecular polymer mortar aggregate.

10. Application of desert sand ceramic aggregate, characterized in that: The ceramic aggregate prepared by the method for preparing desert sand ceramic aggregate as described in claim 1, 5 or 6 is used as a channel fracturing proppant in the oil, natural gas, coalbed methane or shale gas mining industry, or as a thermal insulation material in the construction industry.

Citation Information

Cited By

  • Ceramic polishing sand and preparation method thereof

    CN121673046A